2015
DOI: 10.7448/ias.18.1.20628
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of death recording by health centres and civil registration in South Africans receiving antiretroviral treatment

Abstract: IntroductionThere is uncertainty regarding the completeness of death recording by civil registration and by health centres in South Africa. This paper aims to compare death recording by the two systems, in cohorts of South African patients receiving antiretroviral treatment (ART).MethodsCompleteness of death recording was estimated using a capture–recapture approach. Six ART programmes linked their patient record systems to the vital registration system using civil identity document (ID) numbers and provided d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 43 publications
(55 reference statements)
2
41
0
Order By: Relevance
“…With the linkage data from South Africa this problem is less important: bias will only arise if patients with an ID differ systematically from those without ID and the effect of this bias cannot be minimised by the covariates included in the model. One study found that patients with ID are similar to the patients without ID in terms of their demographic and baseline clinical characteristics [9]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the linkage data from South Africa this problem is less important: bias will only arise if patients with an ID differ systematically from those without ID and the effect of this bias cannot be minimised by the covariates included in the model. One study found that patients with ID are similar to the patients without ID in terms of their demographic and baseline clinical characteristics [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Deaths among patients lost to follow-up are not generally recorded, leading to underestimation of overall, programme-level mortality. Several correction methods to reduce this bias have been proposed [68], which rely on vital status information of a sample of patients lost to follow-up obtained through tracing or data linkages with civil registries [4,5,9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During 1996–2001, approximately 84% of adult deaths were recorded by the vital registration system [34]. The proportion of adult deaths that were recorded increased to approximately 93% after 2001 as a result of intensified efforts of the post-apartheid government to maintain more accurate death records [35]. It is therefore unlikely that many deaths were missed.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa is in a unique position within Africa, being the only country with both a large HIV burden and a well-functioning death notification system, which is estimated to record around 95% of all adult deaths [7]. This makes it possible to obtain reasonably accurate estimates of mortality, which are not biased by the high loss to follow-up observed in many ART cohorts in developing countries [8].…”
Section: Introductionmentioning
confidence: 99%